Application of family whole-exome sequencing for prenatal diagnosis—an analysis of 357 cases - Ge, Yijun; Yuan, Huizhen; Yu, Yao; Xiao, Junfang; Liu, Danping; Peng, Yongbao; Liu, Ying; Huang, Shuhui; Yang, Bicheng; Zou, Yongyi; Liu, Yanqiu (Frontiers in Medicine, 2025)
ObjectiveTranslation of fertility risks through whole-exome sequencing of family lines to identify variants that explain patient’s clinical phenotypes.Methods1. Using techniques such as amniotic fluid, chorionic villus, or umbilical cord blood sampling, intact fetal cells were extracted for cell culture and subsequently analyzed using chromosomal karyotyping and chromosomal microarray techniques. 2. With fully informed consent, fetuses and their parents whose genetic etiology could not be detected by karyotyping combined with chromosomal microarray technology had their cellular DNA subjected to whole-exome sequencing of the pedigree. 3. Pathogenic variants were screened in combination with fetal ultrasound phenotyping and ACMG variant rating guidelines for variant interpretation, followed by inviting multidisciplinary experts to conduct an in-depth analysis and indicate fetal-related ultrasound abnormalities. 4. Genetic counseling is assisted based on the results.Results1. Of the 357 fetuses included in the study, 33 (33/357, 9.24%) had a successful genetic etiology identified through family-wide exome sequencing combined with ultrasound phenotyping. 2. The results showed that skeletal anomalies were the most frequent, accounting for 15 cases (15/33, 45.45%), followed by multiple malformations in 7 cases (7/33, 21.21%), renal anomalies in 3 cases (3/33, 9.09%), soft index anomalies in 2 cases (2/33, 6.06%), neurological anomalies in 2 cases (2/33, 6.06%), cleft lip and palate in 1 case (1/33, 3.03%), cardiac abnormality in 1 case (1/33, 3.03%), hydatidiform mole in 1 case (1/33, 3.03%), and cataract in 1 case (1/33, 3.03%). 3. During whole-exome sequencing, three previously unreported variant sites were identified: MSX2 (NM_002449.4: c.423_427dupCAATC, p.Arg143Profs*39), EVC (NM_153717.2: c.130delC, p.Leu44Phefs*72), and RYR1 (NM_000540.2: c.14129 + 1 G > A).Conclusion1. This study provides robust data supporting the application of whole-exome sequencing of family lines in clinical practice, offering valuable reference information for clinicians. 2. The newly discovered variants significantly enhance the relevant genetic databases. 3. Genetic diagnosis can offer clear guidance regarding the decision to continue with the pregnancy and future reproductive choices.